Strengthening Local Culture through Informal Education in the Era of Society 5.0 - wiwin yulianingsih; Sjafiatul Mardliyah; Ali Yusuf; Diana Rahmasari; Frimha Purnamawati; Ganes Gunansyah; M Fahmi Zakariyah (Universitas Pendidikan Ganesha, 2025)
In the era of Society 5.0, the preservation of local culture faces serious challenges due to the rapid flow of modernization and digitalization. This condition demands an adaptive value transmission strategy to prevent cultural identity from being eroded by developments. This study aims to analyze the role of informal education in strengthening local culture amidst the dynamics of modern society. The study used a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews with 15 informants, and documentation, and analyzed using the Miles and Huberman model. The subjects of this study were traditional leaders, village elders, parents, local youth, and participants in religious rituals. The results show that informal education takes place actively through family roles, involvement in traditional rituals, and intergenerational collaboration. Cultural values are inherited naturally through social practices without relying on the formal education system or digital technology. These findings confirm that community-based informal education is highly effective in maintaining cultural identity and building social resilience. The implications of this study provide a basis for developing contextual educational strategies relevant to the challenges of the digital era and modernization.